Dual-Band Antenna Integrated With Solar Cells for WLAN Applications - An, Wenxing; Wang, Hui; Luo, Yu (Frontiers in Physics, 2021)
A single-port dual-band antenna integrated with solar cells is reported for the 2.4/5-GHz WLAN applications. Thirty solar cells are adopted and integrated into the antenna structure for both energy harvesting and wireless communication. The solar cells can act as a director for the lower band, and the main radiation structure for the higher band. The slot and microstrip antennas are incorporated into the compact structure and multiple resonant modes are utilized for dual-band performance. The measurement results show that the lower band is from 2.27 GHz~2.5 GHz with an omnidirectional radiation pattern and the upper band is from 4.8 GHz~6.9 GHz with a directional radiation pattern. The proposed solar cell antenna can provide a dual-band performance with the ability of DC power generation, which can be a potential candidate for future green low-carbon communication.